Quantitative Genetics Analysis of Autism According to Sex Hormones - A-S. U. Hassan1 , Najat Mohammed Flyyih2, Suhaib Khalid Ibrahim3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The present paper applied the light on 46 rats models induced with autism to prove the relationship amongsex hormones and both of aromatase and RORA. After six practical steps, the results explain a negativerelation of testosterone opposites with positive one for estrogen for their relations on aromatase andRORA. As testosterone rise significantly 3.015±0.321 ng/mL, estrogen declined significantly too to record0.033±0.0011 ng/mL. on the quantitative genetic levels we concluded that both sex hormones affecting thephysiological mechanisms of aromatase reaction and RORA synthesis.